Capital-Skill Complementarity, Income Distribution, and Output Accounting - Fallon, P. R.; Layard, P. R. G. (Journal of Political Economy, 1975)
This article presents evidence for the view that physical capital is more complementary to educated labor than to less educated labor. For this reason previous estimates of elasticities of substitution between educated and less educated labor are too high. Using a two-level CES production function, we run international cross-sectional regressions at the level both of the economy and of individual sectors. The whole-economy model allows for the effects of wages on educational choices as well as vice versa. It predicts that, as total capitalper head rises, the share of physical capital in national income falls and that of human capital rises. The production function also shows that intercountry differences in output per head are due more to differences in physical capital than in human capital.